A Scholar-Practitioner Case Approach: Implications for Advancing Theory and Research Through Informed Practice. (August 2013) - Scully-Russ, Ellen; Lehner, Rachelle; Shuck, Brad
The Problem: Though there is growing interest in the nature of scholarly practice in Human Resource Development (HRD) there is little understanding of how the everyday activities of HRD practitioners are mediated by HRD theories and research. The Solution: This preface provides the framework for this special issue on HRD scholar-practitioners. Each article in this issue, with the exception of the final article by Lombardozzi, presents a real-world case on how HRD scholar-practitioners used HRD theory and research to navigate an intractable problem in their practice. This issue explores the wide and varying ways in which scholar-practitioners approach their work, how research and theory were both applied and extended in practice, and the implications for HRD theory, research, and practice. The Stakeholders: HRD scholars, researchers, and practitioners who are members of the Academy of Human Resource Development (AHRD), as well managers, educators, and higher education administrators who have a stake in effective organizations may gain insight into the nature of HRD scholarly practice and the role of the HRD scholar-practitioner.